New Opportunities for Raptors Conservation in Africa and Eurasia Emerging from the Third Meeting of Signatories - Umberto Gallo-Orsi; Lauren Lopes (Пернатые хищники и их охрана)
The Convention on Migratory Species’ Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia (Raptors MOU) represents a unique international agreement dedicated to the preservation of migratory raptors belonging to the orders Accipitriformes, Falconiformes, and Strigiformes. At the Third Meeting of Signatories to the Raptors MOU (MOS3), held in Dubai from 3 to 6 July 2023, significant progress was made towards advancing commitments for the conservation of these majestic birds. The primary outcomes of MOS3 are summarized below.